Artificial Intelligence-Based Visa Processing System to Reduce Paper Usage, Visa Processing Time, and Human Errors During the Application Review Process - Chollampat, Azeez (Digital Repository of Theses, 2025)
Visa processing is often the most crucial, yet frequently the most challenging, part of international travel. The current visa processing system has several difficulties, including excessive paperwork, frequent travel to visa centres, prolonged processing times, and a high incidence of human errors. These issues are highly inconvenient for applicants, particularly vulnerable groups such as senior citizens, pregnant women, and families with children. It also puts an operational challenge for consulates and service providers. There is an increasing global demand for seamless and sustainable services, as well as a compelling need to redesign the current visa processing system. This thesis presents a framework for an AI-based visa processing system designed to minimize the difficulties of the current visa processing system. The proposed system integrates several cutting-edge artificial intelligence techniques, including Optical Character Recognition (OCR), Natural Language Processing (NLP), and machine learning algorithms. The thesis goes into the architecture, training, and deployment of these AI components, with a strong focus on the accuracy, robustness, and scalability of the system. It also explores hybrid AI approaches that combine multiple techniques such as deep learning models, language transformers, and rule-based systems to handle the complex variability in visa documents. The literature review includes benchmarking of OCR engines and NLP frameworks, as well as an evaluation of real-world use cases and datasets. Beyond the technical implementation, the thesis also addresses challenges related to bias, explainability, and ethical use of AI in administrative decision-making. By integrating environmental sustainability goals using AI, the thesis research proposes a next-generation visa processing system which is faster, greener, and more reliable. That is, the proposed system aims to enhance the user experience for applicants, improving the overall efficiency and transparency of visa processing authorities and making the process much more environmentally friendly.